SET-9 and SET-26 are H3K4me3 readers and play critical roles in germline development and longevity - Wang, Wenke; Chaturbedi, Amaresh; Wang, Minghui; An, Serim; Santhi Velayudhan, Satheeja; Lee, Siu Sylvia (eLife, 2018)
C. elegans SET-9 and SET-26 are highly homologous paralogs that share redundant functions in germline development, but SET-26 alone plays a key role in longevity and heat stress response. Whereas SET-26 is broadly expressed, SET-9 is only detectable in the germline, which likely accounts for their different biological roles. SET-9 and SET-26 bind to H3K4me3 with adjacent acetylation marks in vitro and in vivo. In the soma, SET-26 acts through DAF-16 to modulate longevity. In the germline, SET-9 and SET-26 restrict H3K4me3 domains around SET-9 and SET-26 binding sites, and regulate the expression of specific target genes, with critical consequence on germline development. SET-9 and SET-26 are highly conserved and our findings provide new insights into the functions of these H3K4me3 readers in germline development and longevity.
Keywords: longevity; H3K4me3; germline